Al-Hazf dalam Penafsiran Al-Qur'an: Telaah Kritis atas Konsep al-Hazf dalam Pemaknaan Ayat - Muhammad Iskandar Zulkarnain (Indonesian Journal of Islamic Literature and Muslim Society, 2017)
This article has discussed the application of al-hazf theory in the Exegesis of Qur'an. The fundamental problem of this article is the lack of a study of the significance and the role of al-hazf theory in interpreting the meaning of the Qur'an. The existence of this theory is generally used only to display the types and the samples of al-hazf, without discussion of the role of this theory in interpreting the verses. The results of this study indicate that the significance and the role of al-hazf theory in interpreting the meaning of Qur'anic verses lie in the use of taqdir  (estimated words) in certain spaces so that problematic verses literally can be understood. In addition, the al-hazf  theory also plays a role in interpreting meaning beyond the absence of the word when the Qur'anic verses do not mention it. This role proves the accuracy of the Qur'an that the meaning of "what is mentioned" and "what is not mentioned" in the text reinforce each other. The Qur'anic texts are concise and solid. This makes the difficult texts of Qur'an can understand. Therefore, the al-hazf theory is used to generate significant understanding in the aspects of structure and meaning of Qur’an.